Register to reply

Flexibility 2

by Yh Hoo
Tags: flexibility
Share this thread:
Yh Hoo
#1
May3-12, 11:56 AM
P: 73
1 = √(1)
= √(-1)(-1)
= (√-1)(√-1)
= i.i
= i[itex]^{2}[/itex]
= -1
Is this a correct equation??
anythings wrong with this?
i think theoretically it is correct but it seems like
√(1) = √(-1)(-1)
√(1) = √(1)(1) also!!
so how to explain this??
Phys.Org News Partner Mathematics news on Phys.org
Math journal puts Rauzy fractcal image on the cover
Heat distributions help researchers to understand curved space
Professor quantifies how 'one thing leads to another'
DonAntonio
#2
May3-12, 12:10 PM
P: 606
Quote Quote by Yh Hoo View Post
1 = √(1)
= √(-1)(-1)
= (√-1)(√-1)
= i.i
= i[itex]^{2}[/itex]
= -1
Is this a correct equation??
anythings wrong with this?
i think theoretically it is correct but it seems like
√(1) = √(-1)(-1)
√(1) = √(1)(1) also!!
so how to explain this??


Squaring is a double branched complex variable function, and thus "usual" properties in real numbers can fail miserably.

In this case the problem appears in the third equality: it isn't true without imposing certain restrictive conditions.

DonAntonio


Register to reply

Related Discussions
Flexibility - multiple methods for solutions? General Math 5
Civil Engineering - Matrix Flexibility Method Engineering, Comp Sci, & Technology Homework 0
Flexibility Matrix Mechanical Engineering 3
Flexibility Method question General Engineering 0
Kevlar flexibility Biology, Chemistry & Other Homework 2